IOT-BASED FLOOD MONITORING AND ALERTING SYSTEM USING ARDUINO UNO AND GSM - NUR AIDA ARIFFAH, KAMIS (Universiti Malaysia Sarawak (UNIMAS), 2022)
This project describes on the design and implementation of IoT-based Flood Monitoring and Alerting System using Arduino UNO and GSM which can provide access to reliable information and speed up evacuation process during flood. The main purpose of this project is to investigate the utilization of sensor and IoT-based technology as a monitoring and alerting system. Nowadays, several countries still employs conventional means in detecting flood level by using human observer to conduct observation. Consequently, the information obtained is less accurate and may maximise the adverse effects of flood. Therefore, an IoT-based Flood Monitoring and Alerting System using Arduino UNO and GSM is proposed and designed. This monitoring and alerting system is constructed based on three different sensors namely HC-SR04 Ultrasonic Sensor, DHT11 Temperature and Humidity Sensor and Water Level Sensor. Arduino UNO acts as the microcontroller board and GSM SIM900A can be utilized for sending alert messages to user in the form of SMS. There are four different cases altogether which are extreme low quantity of water, normal level, warning level as well as danger level and users will receive different SMS according to the cases. Call and redial can also be made to user once the water is at danger level. Thus, user is able to monitor the current water level, humidity and temperature at any time after the system was run. Once the red are activated, it indicates that flood will occur soon and evacuation process is necessary. Otherwise, the situation is still not alarming. The main advantage of the system is the affordable production cost and the system’s capability in helping user to avoid uncalled danger related to flood.